Keberadaan Tindak Pidana Perzinaan dalam Koridor Pembaharuan Hukum Pidana - Iman Hidayat (Universitas Batanghari Jambi, 2022)
Custom is the reflection of personality and is one of the reflections of nation soul from century to century. Every nation in the world has its own custom which is not similar from one another, depending on the on the place and the time. This difference is the most important aspect as the identity of a nation. As always happens in the society, there have been many social conflicts in the society of indigenous law because of the violate of the law done by someone or a group of people. The situation will be normal again if the person violate the law has been given indigenous sanction or punishment. Those indigenous violations are mainly caused by the conflicts with what here been agreed together, and which solution has been authorized to the indigoneous institution.